Developing Interest-Based Teaching Materials in Chemistry Ed: Advancing Pedagogical Practices for Pre-service Teachers Engagement - Almubarak Almubarak; Parham Saadi; Yusuf Al Arief; Dini Noor Arini (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2025)
Interest is an essential element in designing chemistry learning. Teaching students based on interest trains sensitivity and as a reinforcement of chemical content, including triggering students' thinking processes through relevant teaching materials. However, the development of teaching materials focused on the interest approach is still limited, especially in chemistry education in higher education. The research method uses the ADDIE development model (analyse, design, develop, implement, evaluate), with data collection techniques using questionnaires, observation, and documentation, including product feasibility criteria (valid, practical, and effective). The data analysis technique uses a quantitative approach, especially in the aspects of validity to product effectiveness. The results show that the products obtained through the development model and show that the product is declared feasible, with a high validity of 88.80%, practical implementation of 94% (aspect of implementation), and effectiveness in learning management of 94% (aspect of teacher ability to manage learning). Developing interest-based teaching materials is a strategic step to improve students' structure and mental models as prospective teachers, including conceptual understanding and intrinsic motivation. Thus, empowerment of interest influences students' thinking ability, which also helps them experience cognitive transformation as an improvement in mental structure and model in understanding context. This research is also a provision to face various global challenges that are increasingly complex and connected.